Olympism, olympic education and learning legacies - Chatziefstathiou, Dikaia; Müller, Norbert, 1946- (Cambridge Scholars Publishing, 2014)
This book is largely a collection of the papers presented at the symposium Olympism, Olympic Education and Learning Legacies, organised by the Comité Internationale Pierre de Coubertin (CIPC). It was held during the London 2012 Olympic and Paralympic Games at Canterbury Christ Church University in Kent, United Kingdom. The symposium drew together presenters and audience members from twenty-five nations on four continents to discuss current and future challenges of education and the Olympic Mo ...